Strengthening Business Sustainability Through Financial Literacy Education: A Study on The Ulos Craftsmen Center In Nagori Rambung Merah, Simalungun - Liharman Saragih; Wico Jontarudi Tarigan (Manajemen: Jurnal Ekonomi USI, 2025)
Providing education to improve financial literacy among MSME actors is one way to deepen their knowledge, which is believed to benefit their businesses, especially in terms of sustainability. This study was conducted at the Ulos Craftsmen Center in Malang using qualitative methods through interviews. Research findings indicate that not all entrepreneurs possess adequate financial literacy, especially in the context of investment. Nevertheless, the financial attitudes of business actors are considered quite good, but not in aspects such as budgeting, cash flow monitoring, and business protection planning. This condition is caused by an excessive focus on business operations, leaving them with insufficient time for those activities. The results of this research are expected to contribute to increasing entrepreneurs' awareness of the essence of financial literacy as a fundamental basis in company financial management to ensure their businesses continue to operate